Additive manufacturing of novel heterostructured martensite-austenite dual-phase steel through in-situ alloying. (December 2022) - Su, Jinlong; Tan, Chaolin; Ng, Fern Lan; Weng, Fei; Chen, Lequn; Jiang, Fulin; Teng, Jie; Chew, Youxiang
Abstract: The interplay between the martensite and austenite phases in steel has critical effects on the mechanical properties. To tune the phase constitutions of martensite and austenite phases, this work in-situ alloyed martensitic C300 maraging steel (MS) with austenitic 316 L stainless steel (SS) laser-directedected energy deposition (LDED). The microstructures, mechanical properties and deformation behaviour of the novel MS-12 wt. % SS (MS12) and MS-24 wt. % SS (MS24) dual-phase steels were investigated. The as-built samples achieve a relative density above 99.9 % and martensite-austenite dual-phase heterostructures. Micro-segregation of molybdenum is considered the dominant reason for the face-centred cubic (FCC) phase formation. The fractions of the FCC phase were 5.8 % and 16.8 % in the MS12 and MS24 alloys, respectively. Moreover, the unique thermal history of LDED induces the heterostructured microstructure with FCC-rich and FCC-lean regions, which contributes to the high work hardenability of the steel. Compared with MS12, MS24 shows a much higher elongation (14.3 %) and a superior work-hardening capability. The in-situ digital image correlation (DIC) observations reveal the strain partitioning within the two alloys during the initial deformation stage. The findings highlight a new approach to developing new materials by in-situ alloying commercially available materials using LDED. Graphical Abstract: ga1